Effects of soil physics, chemistry, and microbiology on soil carbon sequestration in infertile red soils after long‐term cultivation of perennial grasses. Issue 2 (9th December 2022) - Hou, Wei; Xu, Yi; Xue, Shuai; Li, Jie; Yang, Yang; Yi, Zili; Fu, Tongcheng
Abstract: Determining the effect of perennial energy crop (PEC) cultivation on soil organic carbon (SOC) in marginal land soil is vital for carbon neutrality and bioeconomy development. However, a comprehensive and systematic evaluation of the response of SOC content to different PECs and its underlying drivers is still lacking. We used soil data collected from infertile red topsoil (0–20 cm) after 10 years of cultivation with Miscanthus (MS), Panicum virgatum (SG), and Saccharum arundinaceum (SA) to explore the changes in SOC stock induced by PEC. The roles of physical, chemical, and microbiological factors driving the increase in the SOC stock were investigated. Results revealed that SA and MS enhanced SOC stock by 87.97% and 27.52% relative to the uncultivated control. Conversely, PEC increased the percentage of soil mega‐aggregates, geometric mean diameters, soil chelate iron (Fe), and aluminum (Al) oxides, and reduced soil acidity for the infertile red soils. In addition, fungal richness and diversity for PEC soils were enhanced compared to the unplanted soil. It is possible that PEC cultivation reduced the relative abundance of copiotrophic fungi but increased the relative abundance of oligotrophic fungi. Furthermore, variance partitioning analysis revealed that chemical and microbiological factors accounted for 80.54% of the total variation for the SOC stock. The partial least squares path model showed that PEC cultivation enhanced soil carbon (C) stock via soil deacidification and increased soil bacterial function. In conclusion, this study confirms the SOC sequestration potential of PEC cultivation in marginal land and the underlying mechanism driving SOC stock. The main positive factors controlling soil C sequestration included "pH, " while the negative factors were "bacterial community, " "fungal community, " and "bacterial function." Our research may help encourage and support decision‐makers of wasted marginal land conversion to PEC cultivation. Abstract : Long‐term cultivation of Miscanthus and Saccharum arundinaceum increased soil organic carbon stock in infertile red soils. Soil pH is the main factor affecting soil carbon stock in red soils. Soil copiotrophic and oligotrophic microbes significantly shaped by the cultivation of perennial grasses.